Characteristics and genesis of carbonate micropores in the first member of Lower Cambrian Canglangpu Formation in north and central Sichuan Basin - Chunyu ZHOU; Yuan HE; Zongze LI; Gang ZHOU; Dailin YANG; Yiting SUN; Ya ZHANG; Huaguo WEN; Sibing LIU (Shiyou shiyan dizhi)
Micropores with diameters under 10 μm are a current research focus in deeply buried tight reservoirs. The Lower Cambrian Canglangpu Formation in the Sichuan Basin shows considerable potential for natural gas exploration. The abundant micropores in the dolomite of the first member of Canglangpu Formation (Cang 1) serve as the main storage space for natural gas. Therefore, clarifying the development characteristics and genesis mechanisms of micropores is key to identifying favorable exploration areas. Through cast thin-section identification, scanning electron microscopy (SEM) analysis, and core computed tomography (CT) scanning, the study characterized the micropores in the dolomite of the Cang 1 member in the north and central Sichuan Basin. Additionally, the genesis mechanisms were explored considering the sedimentary environments and diagenesis processes. The oolitic dolomite samples from the Cang 1 member in the study area had an average porosity of 3.44%, with a maximum porosity of 9.44%. Cast thin-section analysis indicated poor pore development. However, SEM and CT scanning images revealed the presence of abundant micropores, demonstrating that micropores were the primary contributors to porosity in the oolitic dolomite reservoirs of the Cang 1 member. The reservoir space in the study area is dominated by intercrystalline pores extensively developed in particles. These micropores exhibit triangular or polygonal shapes, with pore diameters mainly ranging from 3 to 9 μm, and are abundant, displaying a dot-like or clustered distribution. On a macroscopic scale, the micropores outline the contours of oolites, indicating that micropores are primarily distributed within particles. The development of micropores in the dolomite of the Cang 1 member was intimately linked to the selective dissolution of oolitic beaches by meteoric freshwater due to sea-level changes in early sedimentary stages. The dolomitization at the burial stage was crucial for micropore formation. The loss of macropores was mainly influenced by compaction, pressure solution, and hydrocarbon charging from the underlying formations.